If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -4y + -9 Reorder the terms: 15 = -9 + -4y Solving 15 = -9 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 15 + 4y = -9 + -4y + 4y Combine like terms: -4y + 4y = 0 15 + 4y = -9 + 0 15 + 4y = -9 Add '-15' to each side of the equation. 15 + -15 + 4y = -9 + -15 Combine like terms: 15 + -15 = 0 0 + 4y = -9 + -15 4y = -9 + -15 Combine like terms: -9 + -15 = -24 4y = -24 Divide each side by '4'. y = -6 Simplifying y = -6
| 12+7x=5(x+2) | | X^2+2x-19=5 | | 3x+2y=23 | | 7k-14=21 | | 1.12+1.25y=0.71 | | -2+(-18)= | | X^2-x-15=0 | | 3x+3y=10 | | 12m+20=-40 | | 36x^2+12x+1=18 | | 4x+4+6x+9=9x+t | | 2x-7=3x+11-7 | | 4x+4+6x+9=9x | | p=4h+4v | | 2m-8=-28 | | -3x-8= | | 3x=4x-7 | | z+3.5=4.7 | | -3+(-10)= | | .875h-.625=2 | | .875-.625=2 | | 1080=5x+4x | | 24=46y-16x | | -13n+20=-11n+38 | | 19b-10=35+22 | | -t+(-7)=-56 | | 15-2h=7 | | 3Iy+3I-12=0 | | -0.7x-4.6=2.1 | | 15-6x= | | (3x+1)-(5x-7)= | | 4x-(8-x)=6-2x |